IMPLEMENTASI KEGIATAN FUN COOKING DALAM MENGEMBANGKAN SOSIAL EMOSIONAL ANAK USIA DINI DI KBI USAMAH KOTA TEGAL - Nisrin Humaida Annur; Abdul Khobir (JURALIANSI: Jurnal Lingkup Anak Usia Dini, 2025)
One of the activities that can develop social emotional is through fun cooking activities at KBI Usamah Tegal City which has implemented fun cooking activities regularly every Wednesday. The purpose of this study is to identify the implementation of fun cooking activities and identify supporting and inhibiting factors of fun cooking activities in developing social emotional early childhood at KBI Usamah Tegal City. The type of research in this study is field research with a descriptive-qualitative approach. Data collection techniques used observation, interviews, and documentation. Primary data were obtained from the principal and educators at KBI Usamah Tegal City. Secondary data were obtained from literature references and supporting documents. The results of the study indicate that the implementation of fun cooking activities in developing social emotional early childhood at KBI Usamah Tegal City consists of three stages, namely planning, implementation, and evaluation. Planning includes determining objectives, menus, and preparation of tools and ingredients. Implementation includes opening activities (prayer, introduction of tools, and habit of washing hands), core (individual/group cooking practice), and closing (prayer, tasting the results of cooking, and cleaning the classroom). Evaluation is carried out through observation and recalling to record the development of children's social emotional. The supporting factors are the availability of infrastructure, teacher creativity, and parental support, while the inhibiting factors are the limited number of accompanying teachers and the limited availability of certain cooking equipment.